Impact of vaginal delivery on pelvic floor musculature in terms of clinical and elastographic changes - Agarwal, Shubhra; Jain, Maryada; Chordiya, Akshata Jaykumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Vaginal delivery imposes considerable strain on pelvic floor musculature, often resulting in structural and functional changes that may contribute to postpartum pelvic floor dysfunction (PFD). This study aimed to assess clinical and elastographic changes in pelvic muscle tone following vaginal delivery. To evaluate the recovery of pelvic floor muscle tone through clinical grading and shear wave elastography (SWE) in primigravida women post vaginal delivery and to correlate both assessment modalities. Methods: A prospective observational study was conducted over 18 months at TMMCRC. Primigravida women with vaginal deliveries were enrolled. Clinical tone (Oxford scale) and elastographic stiffness (kPa) were assessed pre-delivery, 48 hours, 3 months and 6 months postpartum. Data were analyzed using SPSS, with correlations tested with Kappa statistics. Results: The mean age of participants was 24.4±2.8 years and 64% were overweight (BMI>25 kg/m²). Most had a second stage of labor<60 minutes (92%) and spontaneous vaginal delivery (96%). Pre-delivery clinical grading revealed 86% with Grade 2 tone, while elastography showed 64% with ES4 stiffness. At 6 months postpartum, 76% achieved Grade 4 tone and 60% achieved ES1 elasticity, indicating significant recovery (p<0.01). A strong correlation was observed between clinical and elastographic grading (Kappa=0.76, p=0.007). Persistent symptoms included dyspareunia in 14% and stress urinary incontinence in 8%. Conclusions: Pelvic floor muscle tone progressively improved post vaginal delivery. SWE and clinical grading are complementary and reliable for tracking postpartum recovery.